Merancang Bangunan Fasilitas Bermain, Olahraga, dan Pojok Baca sebagai Pusat Interaksi Sosial di Desa Bahu Palawa Kecamatan Kahayan Tengah - Marlina, Nani; Supratman, Muhammad Nugraha Airlangga; Salim, Juantono; Rere, Riska; Hunter, Yuan; Abdul, Agus; Surai, Sapta Nasa; Puspasari, Veronika Happy; Waluyo, Rudi (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
The availability of community facilities that support social, sports, and educational activities is an important need for rural communities, including Bahu Palawa Village, Kahayan Tengah District. This study aims to design a multifunctional building that integrates play facilities, sports, and reading corners as a center for social interaction. The design method includes a participatory approach with data collection through interviews, field observations, and analysis of the needs of the local community. The design results show a building that prioritizes the function of open space for playing, a multi-purpose sports area, and a comfortable and educational reading corner. This design prioritizes desires by utilizing local materials, natural ventilation, and a layout that supports social interaction between residents. This building is expected to be able to improve the quality of life of the community, encourage social participation, and devotion  contributes to the development of villages based on community needs by emphasizing aspects of inclusiveness, inclusiveness, and design efficiency, and has te potential to be a model that can be applied in villages